Glutathione induces GABA release through P2X7R activation on Müller glia. Issue 1 (1st January 2017) - Freitas, Hércules Rezende; de Melo Reis, Ricardo A.
ABSTRACT: The retinal tissue of warm-blooded vertebrates performs surprisingly complex and accurate transduction of visual information. To achieve precision, a multilayered neuroglia structure is established throughout the embryonic development, and the presence of radial Müller (glial) cells ensure differentiation, growth and survival for the neuronal elements within retinal environment. It is assumed that Müller cells serve as a dynamic reservoir of progenitors, capable of expressing transcription factors, differentiating and proliferating as either neuronal or glial cells depending on extrinsic cues. In the postnatal period, Müller glia may re-enter cell cycle and produce new retinal neurons in response to acute damage. In this context, glutathione (GSH), a virtually ubiquitous tripeptide antioxidant, which is found at milimolar concentrations in central glial cells, plays a vital role as a reducing agent, buffering radical oxygen species (ROS) and preventing cell death in severely injured retinal tissues. Despite its antioxidant role, data also point to GSH as a signaling agent, suggesting that GABA release and P2X7 R-mediated calcium inwards occur in Müller cells in a GSH-enriched environment. These phenomena indicate a novel mechanistic response to damage in the vertebrate retinal tissue, particularly in neuron-glia networks.